Efektivitas Pengawasan Keimigrasian terhadap Warga Negara Asing Pemegang Bebas Visa Kunjungan pada Masa Pandemi Covid-19 di Wilayah Kota Denpasar - I Made Aditya Dananjaya; I Nyornan Budiartha; I Nyornan Sutarna (Jurnal Preferensi Hukum, 2021)
The impact of the Covid-19 pandemic has caused many problems such as the lack of immigration control for foreign citizens who have visa-free visits to Bali during this pandemic. Based on the problem, the purpose of this research is to analyze the Indonesian government policy in the field of immigration during the Covid-19 pandemic and the implementation of immigration control of foreign citizens holding visa-free visits during the Covid-19 pandemic in the city of Denpasar. The type applied in this research is empirical law. Sources of data used are primary and secondary data sources. The data collection techniques were carried out by means of interviews, observations, inventory of legal materials. Furthermore, the data are explained by systematic data processing methods. The results showed that the policy adopted by the government was the Regulation of the Minister of Law and Human Rights No. 8 of 2020 concerning Temporary Cessation of Visit Visa and Visit Visa on Arrival and Granting a Stay Permit in a State of Force. The effectiveness of its implementation is not yet effective because immigration can only monitor activities based on data sources from social media and heads of the environment and the data is not accurate, so it needs to be refined using a data application system for mapping foreigners based on the type of residence permit and located in each region. It is hoped that this policy will be the best solution until the pandemic ends.